Health spillover studies of long-term care insurance in China: evidence from spousal caregivers from disabled families - Wenjing Jiang; Hongyan Yang (International Journal for Equity in Health, 2023)
Abstract Background To alleviate the shortage of caregivers associated with disabled persons, China has implemented a pilot policy for long-term care insurance. This policy has the characteristics of "familialization" and "de-familialization" policy orientation, and it is indeed essential to clarify whether the policy has a positive spillover effect on the health of family caregivers, which is of great value to the pilot from local practice to national institutional arrangement. Methods Based on the China Health and Retirement Longitudinal Study microdata and time-varying DID method, our study used the implementation of the pilot policy as a "quasi-natural experiment" to assess the health spillover effects of the pilot policy on family spousal caregivers. Results This policy significantly improved the health of spousal caregivers, increasing self-rated health and life satisfaction, and reducing depression; Compared with female, urban and central-western spousal caregivers, male, rural and eastern spousal caregivers were "beneficiaries" in more dimensional health. Conclusions Our research indicated that spousal caregivers of disabled people, particularly male, rural and eastern spousal caregivers, experienced positive health spillovers after implementing long-term care insurance. These results suggest that the imbalance between supply and demand of nursing staff could be solved in terms of de-familialization and familialization, spousal caregivers should be promoted to equally enjoy the policy benefits on gender, urban–rural and regions.